Penerapan Metode Evaluasi Heuristik Untuk Mengevaluasi Usability Website Medisol - Felycia Wisanto; Mohammad Fajar; Baizul Zaman (KHARISMA Tech, 2023)
The aim of this study is to evaluate the usability of the Medisol website using the Heuristic Evaluation method. Data was collected through questionnaires and literature study. The number of samples in the questionnaire used was 25 respondents who were Medisol website users who had an understanding of the services provided, knowledge of information technology and problem domains or knowledge of drug problems. From the results of calculations using the heuristic method, it was found that the highest proportion was found in the principle of Recognition rather than recall with code H6 of 0.8 which is a cosmetic problem category which means that problems or deficiencies on the Medisol website do not need to be repaired except for time. website project work is still available. The lowest proportion is on the principle of Visibility Of System Status with the H1 code of 0.253, this is not a necessity for the founding team to make improvements because the weight is not the main focus in repairs. The evaluation results show the average value of usability problem ratings (severity rating) found when conducting heuristic evaluations is 0.437, which means usability problems are relatively low where it does not affect the convenience of accessing the Medisol website.